Patient safety when receiving telephone advice in primary care - a Swedish qualitative interview study - Karin Berntsson; Maria Eliasson; Linda Beckman (BMC, 2022)
Abstract Background A lack of patient safety is a significant global public health challenge and is one of the leading causes of death and disability, entailing significant financial and economic costs. However, patient safety can be improved and patients can avoid being harmed if more knowledge could be gained about what it is that impacts patient safety. Patient safety when receiving telephone advice is an important issue given the increase in digitalization in healthcare services. Aim The aim of this study was to explore district nurses' ("telenurses") experiences and perceptions of patient safety when providing health advice over the phone. Methods Data collection was performed using semi-structured interviews and analyzed using qualitative content analysis. The participants (n = 12) were telnurses in primary care. Results The theme "Being able to make the right decision" was formed based on two categories: "Communication" and "Assessment". Through effective communication with the right conditions to make an assessment, the correct decision can be made when a patient calls, and the district nurse feels that their telephone advice is safe for the patient. Conclusions Patient safety can be challenged when receiving telephone advice, particularly when they feel stressed due to organizational factors. There is a need to shift from the individual to the organization. Further, while computerized knowledge support generally results in safe decisions, there may also be problems. Hence, it is imperative to develop computerized knowledge support as a part of improved patient safety in telephone advice.